Geology And The Correlation Between Geological Control And Nickel Quality In Gag Island, Raja Ampat Islands, West Papua - Bambang Kuncoro Prasongko; Agus Harjanto; Muhammad Ghifary Askaria (Universitas Pembangunan Nasional Veteran Yogayakarta, 2022)
The geology of Gag Island, Raja Ampat Islands, West Papua Province is composed of volcanic rocks and ultramafic rocks as carriers of laterite nickel deposits (Supriatna, et al. 1995). The research was conducted by surface mapping supported by drill data, and drill geochemical data. Data collection by surface mapping aims to determine the relationship of geological control to the quality of laterite nickel. The characteristics of laterite nickel deposits are influenced by geological factors in the form of lithology, topography, Drainage drainage, tectonics, and geological structures (Elias, 2002), so that geological control of the quality of laterite nickel deposits needs to be studied further.The research area found 3 rock units in the form of peridotite unit (harzburgite), serpentinite unit, and alluvial deposit unit. The data shows that the highest nickel content is in peridotite (harzburgite) units. In addition, the shape of the land based on the geomorphological aspect shows that in the form of weak wavy hills, laterite deposits are quite well developed and thick. The landform is supported by a relatively sloping slope (0-8 o ) with an undulating morphology and a dendritic Drainage pattern with a content of > 1.5% Ni and a thickness of 9-16 meters, while levels of < 1.5% Ni reach a thickness of 5-22 meters. The geological structure in the morphology is only found in the form of paired joints and filled joints. These joints become an important component in the process of garnierite mineralization as a carrier of Ni.